Financial disciplines teaching methods development by creating a problem situation (Journal of Economic Research & Business Administration, 2016)
The necessity of transition from traditional teaching technology to new concept and human resources development technology – problem teach-ing – is substantiated. The principle of searching educational-cognitive student’s activity, i.e. principle of discovery of science conclusions, activ-ity ways, inventions of new subjects and ways of knowledge application to practice. Using of problem teaching technology in financial disciplines teaching is shown on the example of “Securities market” discipline.
Keywords: problem teaching; problem situation; educational process activization; problems of securities market; securities market.